A novel method to obtain accurate length estimates of carnivorous reef fishes from a single video camera - Trobbiani, Gastón Andres (2015)
In the last years, technological advances enhanced the utilization of baited underwater video (BUV) to monitor the diversity, abundance, and size composition of fish assemblages. However, attempts to use static single-camera devices to estimate fish length were limited due to high errors, originated from the variable distance between the fishes and the reference scale included in the scene. In this work, we present a novel simple method to obtain accurate length estimates of carnivorous fishes by using a single downward-facing camera baited video station. The distinctive feature is the inclusion of a mirrored surface at the base of the stand that allows for correcting the apparent or "naive" length of the fish by the distance between the fish and the reference scale. We describe the calibration procedure and compare the performance (accuracy and precision) of this new technique with that of other single static camera methods. Overall, estimates were highly accurate (mean relative error = -0.6%) and precise (mean coefficient of variation = 3.3%), even in the range of those obtained with stereo-video methods.